An essential role for decorin in bladder cancer invasiveness. Issue 12 (20th October 2013) - El Behi, Mohamed; Krumeich, Sophie; Lodillinsky, Catalina; Kamoun, Aurélie; Tibaldi, Lorenzo; Sugano, Gaël; De Reynies, Aurélien; Chapeaublanc, Elodie; Laplanche, Agnès; Lebret, Thierry; Allory, Yves; Radvanyi, François; et al.
<x xml:space="preserve">Abstract</x> Muscle‐invasive forms of urothelial carcinomas are responsible for most mortality in bladder cancer. Finding new treatments for invasive bladder tumours requires adequate animal models to decipher the mechanisms of progression, in particular the way tumours interact with their microenvironment. Herein, using the murine bladder tumour cell line MB49 and its more aggressive variant MB49‐I, we demonstrate that the adaptive immune system efficiently limits progression of MB49, whereas MB49‐I has lost tumour antigens and is insensitive to adaptive immune responses. Furthermore, we unravel a parallel mechanism developed by MB49‐I to subvert its environment: de novo secretion of the proteoglycan decorin. We show that decorin overexpression in the MB49/MB49‐I model is required for efficient progression, by promoting angiogenesis and tumour cell invasiveness. Finally, we show that these results are relevant to muscle‐invasive human bladder carcinomas, which overexpress decorin together with angiogenesis‐ and adhesion/migration‐related genes, and that decorin overexpression in the human bladder carcinoma cell line TCCSUP is required for efficient invasiveness in vitro. We thus propose decorin as a new therapeutic target for these aggressive tumours.